Rethinking Curriculum Internationalization: Virtual Exchange as a Means to Attaining Global Competencies, Developing Critical Thinking, and Experiencing Transformative Learning. Issue 1 (4th May 2022) - Duffy, Lauren N.; Stone, Garrett A.; Townsend, Jasmine; Cathey, Jamie
Abstract: Virtual exchange and collaborative online international learning have emerged as a means to internationalize campuses and foster the development of global competencies among students by facilitating connections with people, organizations, and institutions abroad. Based on a virtual exchange between the U.S. and Thai undergraduate students, this qualitative research used written individual reflection, focus group data, and observations to explore whether U.S. students developed global competencies in the form of ability to communicate and collaborate in a global and multicultural context. Additionally, this study explored whether the focus on the " process " of the collaborative project allowed for the development of critical thinking skills and whether virtual exchange created opportunities for transformative learning. The findings suggest that the U.S. students in this study developed cross-cultural communication and critical thinking skills, an increased awareness and mindfulness of global and cultural dynamics, higher levels of perceived proficiency in global collaboration, and experienced transformative learning as a result of participating in the virtual exchange project.